PERBAIKAN COUPLING PADA POROS GRINDING WHEEL MESIN GERINDA DATAR REFORM PSGS-4070 AH - Saputra, Aldi Yusuf; Aisyah, Ratu; Yudo, Eko; Ariyanto, Ariyanto (Politeknik Manufaktur Negeri Bangka Belitung, 2025)
The Reform PSGS-4070 AH surface grinding machine in the Mechanical Laboratory of the Bangka Belitung State Polytechnic of Manufacturing is experiencing issues with the grinding wheel not rotating and producing abnormal sounds when activated. Due to this malfunction, the surface grinding machine cannot be used for learning and production processes. The final project aims to identify the cause of the damage and repair the grinding wheel on the surface grinding machine using observation, manual book study, interviews with technicians, and 5 Why analysis methods. The repair was carried out through identification, disassembly, replacement of damaged components, and reassembly. Post-repair testing showed that the grinding wheel had returned to normal rotation, and the abnormal sounds had disappeared. This project also recommends preventive maintenance to maintain the performance of the machine.